2009
DOI: 10.1016/j.jcrs.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Visual function after implantation of an aspheric bifocal intraocular lens

Abstract: The aspheric IOL provided good functional vision at far and near, with lower performance at intermediate distance; good photopic contrast sensitivity and lower mesopic performance; and a low incidence of visual disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 27 publications
8
72
0
3
Order By: Relevance
“…13 Montés-Micó and coauthors 13 reported that patients with multifocal IOLs had worse CSF under dim conditions. Studies evaluating the CSF after hybrid multifocal IOL implants 20,26,29,30,32,35,38,39,43,[46][47][48][49][50] also found a reduction in contrast sensitivity when the luminance level was reduced, particularly for higher spatial frequencies. This trend agrees with classic data on the effect of the luminance level on contrast sensitivity.…”
Section: Contrast Sensitivitymentioning
confidence: 97%
See 3 more Smart Citations
“…13 Montés-Micó and coauthors 13 reported that patients with multifocal IOLs had worse CSF under dim conditions. Studies evaluating the CSF after hybrid multifocal IOL implants 20,26,29,30,32,35,38,39,43,[46][47][48][49][50] also found a reduction in contrast sensitivity when the luminance level was reduced, particularly for higher spatial frequencies. This trend agrees with classic data on the effect of the luminance level on contrast sensitivity.…”
Section: Contrast Sensitivitymentioning
confidence: 97%
“…All studies 20 30,36,38,40 show that the new AcrySof ReSTOR aspheric IOL with a +3.00 D addition provides better intermediate visual performance than AcrySof ReSTOR aspheric IOL with +4.00 D addition, with no decrease for either distance or near visual acuities. It seems that the lower addition of the IOL plays an important role in the improvement of visual acuity for intermediate distances.…”
Section: Hybrid Multifocal Iols Madrid-costa Cerviño Ferrer-blascomentioning
confidence: 97%
See 2 more Smart Citations
“…Bifocal refractive (1)(2)(3) , diffractive (4)(5)(6)(7) , spherical hybrid (8)(9)(10)(11) and aspheric hybrid (12)(13)(14)(15)(16) IOLs generate two focal points along the optical axis to provide good monocular uncorrected distance and near visual acuity (UCVA and UNVA, respectively) as well as functional intermediate vision. The bifocal IOLs have also been implanted in RLE with good results at distance and near vision (17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%